Where do new words like boobage, flamage, ownage come from? Tracking the history of ‑age words from 1100 to 2000 in the OED3 - Chris A. Smith (Lexis: Journal in English Lexicology)
This diachronic lexicographic study aims to analyze the morpho-semantic behaviour of ‑age forms in the OED3. The objective is to provide evidence of the diachronic processes which enabled a loan form to become an independent productive pattern of derivation in English. Using the OED3 as a corpus, a list of all the words ending in ‑age were generated and then filtered to exclude all those that did not undoubtedly carry the ‑age ending. This filtering removed many false results, such as compounds carrying the noun age and the combining form ‑phage, as well as a multitude of derivatives of existing ‑age nouns, leaving a total of 921 definitive ‑age nominal derivatives. A classification of these forms from a morpho-semantic perspective was then carried out with a view to determining the patterns of formation. The classification is based on historical attestation date, on word origin or base word analysis (LOAN, LOAN BLEND, DEVERBAL OR DENOMINAL DERIVATIVE, BLEND, or UNKNOWN) and finally on semantic features (ACTION / RESULT, PAYMENT, QUANTITY, COLLECTIVE). The distribution of these factors over time then allowed me to attempt to answer the following questions. When do language internal derivatives begin? Are the ‑age forms stable over time or do they evolve, and if so in which direction?The findings of this initial morpho-semantic analysis showed that the pattern of ‑age derivation has remained remarkably stable since its beginnings around 1200 until today, with a slight preference for denominal ‑age nouns over deverbal ‑age nouns. While these results tend to confirm pre-existing findings in historical lexical morphology, the following step involved assessing the productivity of ‑age words over time. The novel part of this study was twofold; first focusing on whether ‑age forms are susceptible to semantic change, and secondly focusing on error forms and transmission errors which enabled me to consider the evidence of historical productivity. In the final section these productivity concerns were extended to contemporary English via a Web Crawler corpus so as to investigate whether ‑age forms continue to exhibit similar behaviour or whether new patterns can be determined. Three major findings stand out.1) So-called obsolete vage forms in the OED3 are not obsolete after all, showing the remarkable productivity and adaptability of ‑age forms over the centuries;2) ‑age words follow a reliable semantic pattern, fitting into four main categories of ACTION / RESULT, TAX / RIGHTS / PAYMENT, STATUS / POSITION, COLLECTIVE / QUANTITY. There is a predictable relation between base word and derivative, which may explain the continued success of ‑age forms, in that they can be used in slang, technical usage, etc. Their remarkable adaptability allows for a sense to be directly dependent on a context, as exemplified by the usage of ownage, or rakeage in English Web 2013; 3) ‑age forms are not very polysemous, they remain transparent in their relation to the base word. They also appear to be less likely to be lexicalized given this transparency. This low rate of lexicalization is a sign of high productivity and may also explain the high rates of obsolescence of historical ‑age words in the OED3.